STRENGTHENING PUBLIC INTEGRITY: THE MODERATING ROLE OF ORGANIZATIONAL COMMITMENT ON DETERMINANTS OF FRAUD PREVENTION - Pertiwi, Devi; Trisnaningsih, Sri; Sulistyowati, Erna (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Fraud remains a persistent challenge in Indonesia’s public sector, requiring robust systems and ethically committed personnel. This study examines the effects of competence, internal control systems, and whistleblowing mechanisms on fraud prevention within the Inspectorate of East Java Province, with organizational commitment as a moderating variable. A quantitative design was used, collecting primary data through questionnaires from civil servants. Data were analyzed using Moderated Regression Analysis (MRA) with SmartPLS 4.0. Results show that competence and internal control systems have a positive and significant impact on fraud prevention, while the whistleblowing system has a positive but non-significant effect. Organizational commitment strengthens the influence of competence and internal control systems but weakens the effect of the whistleblowing system. These findings highlight the need to enhance personnel competence and control frameworks, and to improve whistleblowing accessibility, protection, and credibility, fostering an organizational culture that upholds integrity and effectively mitigates fraud.